2019
DOI: 10.1111/acps.13013
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of bipolar I disorder and conduct disorder: a familial risk analysis

Abstract: of bipolar I disorder and conduct disorder: a familial risk analysis Objective: To investigate the association between pediatric bipolar I (BP-I) disorder and conduct disorder (CD) using familial risk analysis. Method: We compared diagnoses in relatives of youth in four proband groups defined by the presence or absence of BP-I and CD: (1) probands with neither CD nor BP-I (probands: N = 550; relatives: N = 1656), (2) probands with CD and without BP-I (probands: N = 40; relatives: N = 127), (3) probands with BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In a series of manuscripts, we systematically explored all the comorbidities present in youth diagnosed with bipolar disorder (Wilens, Biederman, Forkner, et al, 2003): conduct disorder (Biederman, Mick, Prince, et al, 1999;Biederman, Faraone, Wozniak, & Monuteaux, 2000;Biederman, Fitzgerald et al, 2018;; T. J. Wozniak et al, 2001Wozniak et al, , 2019, substance use disorders (T. Spencer et al, 1999;Wilens et al, 2004Wilens et al, , 2016, anxiety disorders Harpold et al, 2005;Joshi, Mick, Wozniak, Geller, et al, 2010;Joshi, Wozniak, Petty, Vivas, et al, 2010;Wozniak et al, 2002), and autism spectrum disorder (Joshi, Biederman, Petty, Goldin, et al, 2013;Joshi et al, 2018;. We explored the differences between unipolar and bipolar depression (Biederman et al, 2014;Wozniak et al, 2004).…”
Section: Pediatric Bipolar Disorder (By Janet Wozniak Md)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of manuscripts, we systematically explored all the comorbidities present in youth diagnosed with bipolar disorder (Wilens, Biederman, Forkner, et al, 2003): conduct disorder (Biederman, Mick, Prince, et al, 1999;Biederman, Faraone, Wozniak, & Monuteaux, 2000;Biederman, Fitzgerald et al, 2018;; T. J. Wozniak et al, 2001Wozniak et al, , 2019, substance use disorders (T. Spencer et al, 1999;Wilens et al, 2004Wilens et al, , 2016, anxiety disorders Harpold et al, 2005;Joshi, Mick, Wozniak, Geller, et al, 2010;Joshi, Wozniak, Petty, Vivas, et al, 2010;Wozniak et al, 2002), and autism spectrum disorder (Joshi, Biederman, Petty, Goldin, et al, 2013;Joshi et al, 2018;. We explored the differences between unipolar and bipolar depression (Biederman et al, 2014;Wozniak et al, 2004).…”
Section: Pediatric Bipolar Disorder (By Janet Wozniak Md)mentioning
confidence: 99%
“…Biederman, Mick, Wozniak et al, 2003; Biederman, Mick, Faraone, et al, 2006; T. J. Spencer et al, 2001; Wozniak et al, 2001, 2019), substance use disorders (T. Spencer et al, 1999; Wilens et al, 2004, 2016), anxiety disorders (Biederman, Wozniak, Martelon, et al, 2013; Harpold et al, 2005; Joshi, Mick, Wozniak, Geller, et al, 2010; Joshi, Wozniak, Petty, Vivas, et al, 2010; Wozniak et al, 2002), and autism spectrum disorder (Joshi, Biederman, Petty, Goldin, et al, 2013; Joshi et al, 2018; Joshi, Biederman et al, 2012; Wozniak et al, 1997).…”
Section: Pediatric Bipolar Disorder (By Janet Wozniak Md)mentioning
confidence: 99%
“…Regarding comorbidity, two broad patterns have been described, the first with ADHD and disruptive behavior disorders, such as ODD and Conduct Disorder (CD), and the second with anxiety disorders, which may define specific subtypes and developmental pathways of BD [ 11 ]. The first pattern includes preexisting ADHD [ 12 , 13 , 14 ], with rates ranging from 30% to 90%, often associated with ODD and/or conduct disorder (CD) [ 15 , 16 ]. The second pattern of comorbidity includes anxiety disorders, often multiple [ 17 , 18 ], and obsessive compulsive disorder (OCD) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second pattern of comorbidity includes anxiety disorders, often multiple [ 17 , 18 ], and obsessive compulsive disorder (OCD) [ 19 ]. Multiple anxiety disorders (MAD) have been more closely related to bipolarity [ 16 , 17 , 20 , 21 ]. The rates of ADHD comorbidity are particularly high in prepubertal children [ 12 , 22 ], and are confirmed when children are assessed after removing overlapping symptoms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a USA based study on 26 bipolar youths aged 8-13, it was concluded that CD may co-exist with bipolar disorder (BD) at 69% lifetime comorbidity and 54% for episode comorbidity 2 . Bipolar 1 disorder and CD co-existence may represent a distinct subtype of either disorder in terms of presentation, course and treatments 3,4 . The combination of CD and BD in youth predicts high risks of substance use disorders in relatives suggesting a genetic predisposition 5 .…”
mentioning
confidence: 99%